Strengthening Of Marketing Information Systems and Accounting Information Systems for Micro Small and Medium Enterprises (UMKM) Food Culinary Makassar - Rustan, Rustan; Aisyah, Siti; Adiningrat, Andi Arifwangsa; Rustam, Andi; Anggoro, M. Yusuf Alfian Rendra (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to determine the implementation of a marketing information system in increasing the turnover of Micro, Small and Medium Enterprises (MSMEs). The time and place of this research was carried out for two months in several 7 Food Culinary SMEs in Makassar City. Data collection techniques were carried out by means of library research, interviews and field observations. The analytical method used in this research is multiple linear regression analysis. Linear regression analysis method the analytical method that will be used by the author is an applied qualitative descriptive method. The data analysis was carried out using qualitative data analysis. There are several subsystems in increasing the turnover of MSMEs through marketing outputs, namely the product subsystem, the price subsystem, the place subsystem, the promotion subsystem and the marketing mix. Marketing information systems have several functions in a business, namely assessing information needs, developing needed information, and distributing information. The results of the study indicate that strengthening the marketing information system can increase the turnover of MSMEs. marketing output accounting information system, namely product subsystem, price subsystem, place subsystem, promotion subsystem and marketing mix. Meanwhile, the application of accounting information systems can be carried out starting from recording transactions, grouping to preparing financial statements.